Primary thymic mucosa-associated lymphoid tissue lymphoma with multiple thin walled lung cysts: case report and literature review - Kang, Lung-Yun; Ho, Szu-Pei; Chou, Yi-Pin (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Mucosa-associated lymphoid tissue (MALT) lymphoma of the thymus is rare. We reported a case of a 37-year-old Chinese female with Sjögren’s syndrome and hyperglobulinemia. She suffered from chronic cough for 3 weeks. Chest computed tomography (CT) demonstrated a multiloculated cystic mass in mediastinum prevascular space and multiple lung cysts. Laboratory exam of autoimmune markers showed positive of antinuclear antibody (ANA), Sjögren’s syndrome A (SSA), Sjögren’s syndrome B (SSB), and rheumatoid factors (RF). Thymectomy with lymph node dissection was performed. The pathology report revealed thymic extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue. Under immunohistochemical stains, CD20 and Bcl-2 were positive. No evidence of recurrence of disease was found.